Retinal Morphometric Markers of Crystallized and Fluid Intelligence Among Adults With Overweight and Obesity - Jones, Alicia R.; Robbs, Connor M.; Edwards, Caitlyn G.; Walk, Anne M.; Thompson, Sharon V.; Reeser, Ginger E.; Holscher, Hannah D.; Khan, Naiman A. (Frontiers in Psychology, 2018)
Objective: To investigate the relationship between retinal morphometric measures and intellectual abilities among adults with overweight and obesity. Methods: Adults between 25-45 years (N=55, 38 females) with overweight or obesity (BMI ≥25.0 kg/m2) underwent an optical coherence tomography (OCT) scan to assess retinal nerve fiber layer (RNFL) volume, ganglion cell layer (GCL) volume, macular volume, and central foveal thickness. Dual-Energy X-ray Absorptiometry was used to assess whole-body adiposity (%Fat). The Kaufman Brief Intelligence Test-2 was used to assess general intelligence (IQ), fluid, and crystallized intelligence. Hierarchical linear regression analyses were performed to examine relationships between adiposity and intelligence measures following adjustment of relevant demographic characteristics and degree of adiposity (i.e., %Fat). Results: Although initial bivariate correlations indicated that %Fat was inversely related to fluid intelligence, this relationship was mitigated by inclusion of other demographic factors, including age, sex, and education level. Regression analyses for primary outcomes revealed that RNFL was positively related to IQ and fluid intelligence. However, only GCL was positively related to crystallized intelligence. Conclusion: This work provides novel data linking specific retinal morphometric measures – assessed using OCT – to intellectual abilities among adults with overweight and obesity.